ANALISIS PENGARUH DANA PIHAK KETIGA (DPK), CAPITAL ADEQUACY RATIO (CAR), DAN NON PERFOMING FINANCING (NPF) TERHADAP PEMBIAYAAN (STUDI PADA BUS DAN UUS DI INDONESIA PERIODE 2014-2018) - Zuwardi Zuwardi; Hardiansyah Padli; Mohammad Aliman Shahmi (IAIN Batusangkar, 2019)
This study aims to analyze the factors influencing financing on BUS and UUS in Indonesia. Exogenousvariables in this study are Third Party Funds (DPK), Capital Adequacy Ratio (CAR), and Non-PerformingFinancing (NPF), while endogenous variables are financing. This study used secondary data consisted monthlydata of BUS and UUS in 2014-2018. This data is taken from SHARIA banking statistics released by the OJK. Theresearch results obtained that DPK and CAR significantly and positively affect long term financing. While NPFhas no significant effect on long term financing. DPK and NPF also have a positive and significant impact onshirt term financing. Another result was CAR has no significant effect on short term financing.